Efficacy, safety and cost-effectiveness of vonoprazan vs Proton Pump Inhibitors in reflux disorders and H. pylori eradication: A literature review. (October 2022) - Shehryar, Muhammad; Ahmad, Rana Uzair; Kareem, Hira Khalid; Khan, Laiba; Ashraf, Muhammad Fawad; Hassan, Ahtizaz; Saeed, Sabeena; Tareen, Haseeb Khan; Nazir, Dr Adnan; Ashraf, Muhammad Aizaz
Abstract: Gastroesophageal reflux disease (GERD) is one of the most prevalent conditions worldwide and is conventionally treated by proton pump inhibitor therapy. However, around 40% of people have reported some form of resistance to this therapy. Vonoprazan has recently been approved for the treatment of GERD. Literature was searched on PubMed, Google Scholar, Embase and Medline. Inclusion criteria were 1) Human subjects; 2) papers published in English language; 3) study types that are RCTs. In pre-clinical studies, VPZ was unaffected by changes in pH, making it 1.2–2 times more potent than PPI, both in-vivo and in-vitro. In studies involving GERD, several RCTs proved higher efficacy of VPZ than conventional PPI. RCTs on patients affected by H. Pylori showed a higher efficacy than VPZ (95.8%) as compared to PPI (69.6%). In another RCT, adverse effects including diarrhea, nausea and body rash were observed in 32.7% of the people taking VPZ as compared to 40.5% of the people taking PPI. VPZ was shown to be much more cost effective as compared to PPI. This article concludes that VPZ is superior to PPI in terms of efficacy, safety and cost-effectiveness in reflux disorders and H. pylori eradication. Hence, use of vonoprazan should be preferred over conventional PPIs in these disorders. As most of the research was conducted in Japan, studies should be carried out in different regions of the world to explore if these results are extrapolated in those regions. Research is also needed to explore the efficiency of VPZ in scenarios of PPI resistance. Highlights: Gastroesophageal reflux disease is one of the most prevalent conditions worldwide which is conventionally treated by proton pump inhibitor therapy. However, around 40% of people have reported some form of resistance to this therapy. Vonoprazan (aka TAK-438), has been approved for clinical use in Japan to reduce intragastric pH. VPZ is a potassium-competitive acid blocker (P-CAB). This review article suggests that Vonoprazan is 400 times more efficacious than PPIs. The safety profile of Vonoprazan in Reflux Gastritis is just similar to that of PPI use. Also, VPZ is much more cost-effective as compared to PPI's.